Peripheral Blood Telomere Content Is Greater in Patients With Endometriosis Than in Controls. (December 2014) - Dracxler, Roberta C.; Oh, C.; Kalmbach, K.; Wang, F.; Liu, L.; Kallas, E. G.; Giret, M. T. M.; Seth-Smith, M. L.; Antunes, D.; Keefe, D. L.; Abrao, M. S.
The etiology of endometriosis remains poorly understood but circulating stem cells may contribute. Telomeres shorten with cell divisions and age. Stem cells attempt to compensate for telomere attrition through the action of telomerase. Since circulating stem cells may contribute to endometriosis, we compared telomere content in lymphocytes of patients with and without endometriosis. Methods: Observational study comparing peripheral lymphocytes telomere content, measured by quantitative polymerase chain reaction, in patients with (n = 86) and without endometriosis (n = 21). Findings: Patients with endometriosis had longer telomeres than that of matched, endometriosis-free controls (telomere to single copy gene ratio [T/S ratio] of 1.62 vs 1.34, respectively, P = .00002). Patients with endometriosis were 8.1-fold more likely to have long telomeres. (odds ratio = 8.1, 95% confidence interval: 1.28-51.57, P = .0264). Interpretation: Longer telomeres could be consistent with a stem cell origin of endometriosis.